Technology and Power Play in the International System: A Study of the 20th and 21st Centuries - Grace Yusuf; Nancy Oluchi Iwegbunam; Joel Abah (Centre for Behaviour and Wellness Advocacy, 2017)
Globalization has led to a profound diffusion of technological innovations among State and Non-state actors. This has a resultant impact on the arrangement of the distribution of power in the International System. History captures continuous transition in the distribution of power between states in the International System; from a multi-polar system during the first and Second World War, to the bipolar system of the cold war and the uni-polar system that emerged in the aftermath of the cold war. The emergence of new actors in the international system and the change in technological nature and application is ushering in a new era of 'Non-polarity' in the International System. The aim of this paper is to consider the evolving dynamics of the distribution of power in the International System while considering the roles technology has to play. The paper relays the conceptualization of basic terms, and then applies the 'Balance of Power theory' as its theoretical thrust. Finally, it expands on the role of technology in the distribution of power in the International System and what it entails for the future.